2017
DOI: 10.1115/1.4037861
|View full text |Cite
|
Sign up to set email alerts
|

Transient Thermal Modeling of Ball Bearing Using Finite Element Method

Abstract: Gas turbines are fitted with rolling element bearings, which transfer loads and supports the shafts. The interaction between the rotating and stationary parts in the bearing causes a conversion of some of the power into heat, influencing the thermal behavior of the entire bearing chamber. To improve thermal modeling of bearing chambers, this work focused on modeling of the heat generated and dissipated around the bearings, in terms of magnitude and location, and the interaction with the components/systems in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The TNM derives heat balance equations for various complex problems based on electrical laws. 5 Pouly et al 6 studied the power losses in high-speed bearings with the TNM and found that the rolling friction and drag force losses were the two main losses compared to the other sources of power losses. This method simplifies the heat exchanges and is usually applied to analyse the steady and transient temperature field of a working bearing based on the assumption of one-dimensional geometries.…”
Section: Ta Harris Calculated the Frictionmentioning
confidence: 99%
See 2 more Smart Citations
“…The TNM derives heat balance equations for various complex problems based on electrical laws. 5 Pouly et al 6 studied the power losses in high-speed bearings with the TNM and found that the rolling friction and drag force losses were the two main losses compared to the other sources of power losses. This method simplifies the heat exchanges and is usually applied to analyse the steady and transient temperature field of a working bearing based on the assumption of one-dimensional geometries.…”
Section: Ta Harris Calculated the Frictionmentioning
confidence: 99%
“…: the angular velocity of shaft1, in rad/s. Following the SKF model, 4 the total frictional torque M of the deep groove ball bearing 6016 can be calculated with equation (5). The M seal component is ignored in this study since there are no seals in the bearing used in this study.…”
Section: Model Of Power Loss Caused By the Generation Of Heat By Fricmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important factor which determines the bearing behavior in terms of dynamics and mechanical power losses and thermal effects is the lubricant flow rate. Sibilli and Igie 19 developed a formulation able to estimate the heat due to friction taking into account design parameters. Zhou et al.…”
Section: Introductionmentioning
confidence: 99%
“…Another important factor which determines the bearing behavior in terms of dynamics and mechanical power losses and thermal effects is the lubricant flow rate. Sibilli and Igie 19 developed a formulation able to estimate the heat due to friction taking into account design parameters. Zhou et al 20 proposed a measurement method for temperature distribution of bearing inner and outer rings and investigated the influence of applied load and rotating speed on temperature distribution.…”
Section: Introductionmentioning
confidence: 99%